Introduction to nuclear and particle physics - Das, Ashok, 1953-; Ferbel, Thomas (River Edge, N.J. : World Scientific, 2003)
The original edition of Introduction to Nuclear and ParticlePhysics was used with great success for single-semester courses onnuclear and particle physics offered by American and Canadianuniversities at the undergraduate level. It was also translated intoGerman, and used overseas.
Rutherford scattering -- Nuclear phenomenology -- Nuclear models -- Nuclear radiation -- Applications of nuclear physics -- Energy deposition in media -- Particle detection -- Accelerators -- Properties and interactions of elementary particles -- Symmetries -- Discrete transformations -- Neutral kaons, oscillations, and CP violation -- Formulation of the standard model -- Standard model and confrontation with data -- Beyond the standard model.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Nuclear physics; Particles (Nuclear physics); Nuclear Physics; Elementary Particles; Physique nucléaire.; Particules (Physique nucléaire); nuclear physics; particle physics; SCIENCE -- Physics -- Nuclear; SCIENCE -- Physics -- Atomic & Molecular; Particles (Nuclear physics); Physique nucleaire; Particules (Physique nucleaire); Nuclear physics; Nuclear physics; Particles (Nuclear physics); Nuclear physics